2019
DOI: 10.1103/physrevlett.123.096801
|View full text |Cite
|
Sign up to set email alerts
|

Designing Multifunctionality via Assembling Dissimilar Materials: Epitaxial AlN/ScN Superlattices

Abstract: First-principles calculations are performed to investigate the effect of epitaxial strain on energetic, structural, electrical, electronic and optical properties of 1 × 1 AlN/ScN superlattices. This system is predicted to adopt four different strain regions exhibiting different properties, including optimization of various physical responses such as piezoelectricity, electro-optic and elasto-optic coefficients, and elasticity. Varying the strain between these four different regions also allows the creation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Moreover, one can also estimate the intrinsic breakdown field of such systems empirically, which depends on the band gap [47]. Our predicted gap of 3.1 eV after correction (to account for the typical underestimation of LDA) of the 1×1 AlN/ScN superlattice ground state [27] yields an intrinsic breakdown field, E break , of 6.3 MV/cm, which will be the maximum fields considered here. Note that the estimated breakdown field is reasonable since (1) Yazawa et al reported the highest applied electric field (∼6 MV/cm) in epitaxial Al 0.7 Sc 0.3 N film [28]; and (2) Yasuoka et al also reported very large coercive fields of the order of 4-7 MV/cm and maximum applicable electric fields of the order 5-10 MV/cm in Al 1−x Sc x N films [29].…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, one can also estimate the intrinsic breakdown field of such systems empirically, which depends on the band gap [47]. Our predicted gap of 3.1 eV after correction (to account for the typical underestimation of LDA) of the 1×1 AlN/ScN superlattice ground state [27] yields an intrinsic breakdown field, E break , of 6.3 MV/cm, which will be the maximum fields considered here. Note that the estimated breakdown field is reasonable since (1) Yazawa et al reported the highest applied electric field (∼6 MV/cm) in epitaxial Al 0.7 Sc 0.3 N film [28]; and (2) Yasuoka et al also reported very large coercive fields of the order of 4-7 MV/cm and maximum applicable electric fields of the order 5-10 MV/cm in Al 1−x Sc x N films [29].…”
mentioning
confidence: 98%
“…This would require the nonlinear dielectrics to have large ε r and high E break [11][12][13][14][15][16]. A promising candidate is the III-V semiconductor-based systems made by mixing AlN and ScN to form Al 1−x Sc x N solid solutions or AlN/ScN superlattices, that have been attracting much attention due to their potential for high piezoelectric and electro-optic responses [20][21][22][23][24][25][26][27][28][29]. Note that a recent experiment observed a ferroelectric switching in Al 1−x Sc x N films, with a remnant polarization reaching a very large value -in excess of 1.0 C/m 2 [25] -which contrasts with the case of pure AlN that is of wurtzite-type structure [30,31] and is polar but not ferroelectric.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[9] To avoid the configuration-dependent property variation, the AlN/ScN superlattice (SL), the ordered structure, was also recently studied. [10,11] However, both studies focused on the effect of strain in a fixed composition of an (AlN) 1 /(ScN) 1 SL. The problem of the concomitant reduction in the P s (and P r ) by the incorporated Sc in the (Al,Sc)N might be less severe in SL than in SS.…”
mentioning
confidence: 99%